2022
DOI: 10.1155/2022/5365024
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Abiotic Stress Factors on GC-MS-Detected Phytoconstituents of Aloe greatheadii var: davyana Using Heat Map and Hierarchical Clustering Dendrogram

Abstract: Aloe greatheadii var. davyana or spotted aloe is indigenous to South Africa and widely distributed in the northern provinces. The plant has a vast ethnopharmacological application which is mostly attributed to its phytochemical content. The aim of the study was to examine the effect of abiotic stress factors on the plant’s phytochemical content. The phytochemical content of A. greatheadii hexane extracts from four different provinces (Limpopo, Mpumalanga, Gauteng, and North West), harvested from the wild at va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The mass accuracy of all assigned components was less than 5 ppm, relative to the empirical molecular formulas of the compounds known to exist in DG. To present the level of change in the differential compounds, a heat map was generated to show the relative levels of each compound in CHDG and VPDG [ 43 ] ( Figure 4 ). The intensities of ions a and b were higher in VPDG than those in CHDG, indicating that the two components correlated to ions a and b could be used as potential characteristic markers to distinguish between VPDG and CHDG.…”
Section: Resultsmentioning
confidence: 99%
“…The mass accuracy of all assigned components was less than 5 ppm, relative to the empirical molecular formulas of the compounds known to exist in DG. To present the level of change in the differential compounds, a heat map was generated to show the relative levels of each compound in CHDG and VPDG [ 43 ] ( Figure 4 ). The intensities of ions a and b were higher in VPDG than those in CHDG, indicating that the two components correlated to ions a and b could be used as potential characteristic markers to distinguish between VPDG and CHDG.…”
Section: Resultsmentioning
confidence: 99%
“…Heatmap cluster analysis is a popular strategy to cluster medicinal plants based on their biological activities [ 40 ]. It is an efficient tool to facilitate the comparison between plant extracts [ 41 ]. Benabderrahim and collaborators [ 22 ] have used heatmap clustering of plant extracts based on phenol compound composition and antioxidant activity to identify two main clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Heat maps are particularly useful in condensing large amounts of information into a concise visual representation, and have been applied to gene expression, sequencing, geographic data, and population densities [ 48 ]. To better understand the complex relationships described by machine learning models, we proposed utilizing dendrograms and heat maps to describe the gain, cover, and frequency of covariates [ 49 , 50 ]. We found that the cluster produced by the dendrogram is similar to that produced by the SHAP value.…”
Section: Discussionmentioning
confidence: 99%